Gender diversity and syphilis: something's going on? - de Dios-Aguado, Mercedes; Cunha-Oliveira, Aliete; Cotto-Andino, Maylene; Gama de Sousa Aperibense, Pacita Geovana; de Almeida Peres, Maria Angélica; Gómez-Cantarino, Sagrario (Frontiers in Sociology, 2023)
This article aims to analyze the influence of syphilis among people with sexual and gender diversity, different from the binary dimension. Materials and Methods: A scoping review was conducted as a method to address the objective of the study, based on the Dialectical Structural Model of Care (DSM) to obtain the phenomenon from the perspective of cultural history. Results: The review allowed for the analysis of 98 documents, of which 40 texts were used. The construction of sex and gender in Western civilization is based on the Judeo-Christian tradition, which allowed many people throughout history to be persecuted and mistreated for living a lifestyle different from that dictated by religious and traditional canons. Thus, throughout history, homosexuals and prostitutes have suffered segregation, mockery, aggression, and health problems, including syphilis. Conclusions: Despite having a treatment and cure, this pathology has stood the test of time and has remained a secret, obscure and difficult to detect disease, which is still very much present in people of all social classes. It is necessary to re-view history to understand the reasons why syphilis is still prevalent in different societies today.